Menyongsong Era Digital: Mengungkap Potensi Melalui Kurikulum Belajar Mandiri di Pendidikan Sekolah Menengah Kejuruan - Dinna Amalia; Enung Hasanah (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This study aims to dig up information about the independent curriculum, especially in learning computer and telecommunications network techniques in Vocational High School (VHS). This research method uses qualitative methods. Data collection techniques used are observation and interviews. The information obtained is processed and analyzed through several stages, including data reduction, presentation, and conclusion. The study results show that the implementation of the independent curriculum in learning communication and telecommunication network techniques is carried out following the Independent Curriculum Implementation policy from the Ministry of Education, Research and Technology, Indonesia. However, its implementation still needs to be comprehensive. The school needs help learning communication and telecommunications network techniques per the independent curriculum due to a lack of teacher competency and weak infrastructure support. The school has difficulty developing learning methods that create a working atmosphere in the industry so that students can be enthusiastic about participating in the learning process in computer network engineering and telecommunications.